Prodorylaimus filamentus sp. n. and Eutobrilus longicaudatoides sp. n. (Nematoda) from Lake Baikal, Russia - Gagarin, Vladimir G.; Naumova, Tatyana V. (Zootaxa, 2011)
Two nematode species found in Lake Baikal, Russia are described. Prodorylaimus filamentus sp. n. is morphologically close to P. longicaudatoides Altherr, 1968 and P. kralli Tsalolikhin, 1975. The new species can be separated from P. longicaudatoides by the longer body (L = 4.89–6.06 mm versus L = 2.0–3.5 mm), relatively longer tail (c′ = 18.4–25.0 versus c′ = 14–18), longer odontostyle (60–65 µm long versus 32–37 µm long), presence of double and wide guiding ring and longer spicules (89–90 µm long versus 70–78 µm long). It can also be separated from P. kralli by the longer tail (c = 4.3– 6.0, c’ = 18.4–25.0 versus c = 7.0–8.0, c′ = 11–16), lower “vulva-anus to tail length” ratio (1.6–2.2 versus 2.5–3.0), shorter odontostyle (60–65 µm long versus 75–80 µm long). Eutobrilus longicaudatoides sp. n. is closely related to E. anguiculus Tsalolikhin, 1977, but is clearly distinct in the shorter outer labial setae (9–10 µm long or 45–52% of the labial region diameter versus 15–20 µm long or 50–60 % of the labial region diameter), longer tail (males, c = 5.3–5.5, c’ = 11.4–11.8, females, c = 4.5–6.3, c′ = 15.1–16.7, versus males, c = 7.4–10.4, c′ = 8–9, females, c = 5.0–7.7, c′ = 10–12), smaller number of supplements (5 versus 6) and shorter spicules (47–53 µm long versus 66–68 µm long).